2018
DOI: 10.1051/0004-6361/201730580
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal heat flux effects on temperature evolution of the solar atmosphere

Abstract: Context. Heat flux is one of the main energy transport mechanisms in the weakly collisional plasma of the solar corona. There, rare binary collisions let hot electrons travel over long distances and influence other regions along magnetic field lines. Thus, the fully collisional heat flux models might not describe transport well enough since they consider only the local contribution of electrons. The heat flux in weakly collisional plasmas at high temperatures with large mean free paths has to consider the nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This occurs as the most energetic electrons have the longest mean-free paths, and this effect is not captured by flux limiters. The non-local energy transport models used in solar 1D ( (Karpen and Devore, 1987;West et al, 2004)) and 3D (Silva et al, 2018) models have relied on the kernel model derived for laser-plasmas (Luciani et al, 1983), commonly referred to as the LMV model. In this model, the heat flux is calculated by convolving the local conduction with a non-local kernel.…”
Section: Non-local Kernel Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs as the most energetic electrons have the longest mean-free paths, and this effect is not captured by flux limiters. The non-local energy transport models used in solar 1D ( (Karpen and Devore, 1987;West et al, 2004)) and 3D (Silva et al, 2018) models have relied on the kernel model derived for laser-plasmas (Luciani et al, 1983), commonly referred to as the LMV model. In this model, the heat flux is calculated by convolving the local conduction with a non-local kernel.…”
Section: Non-local Kernel Modelsmentioning
confidence: 99%
“…Thus, kernel-based models are able to capture the nonlocal effect, but there remain free parameters, such as a in the LMV model, and there is no unique choice of kernel universally proven to be optimal in all conditions. 3D flare simulations (Silva et al, 2018) have included LMV style non-local electron transport in MHD flare models and shown that this significantly changes the predictions for the temperature of the transition region and upper chromosphere.…”
Section: Non-local Kernel Modelsmentioning
confidence: 99%
“…For instance, in Botha et al (2011) the authors performed numerical simulations and found that thermal conduction plays an essential role in the kink instability of coronal loops. Also, in Silva et al (2018), the authors found that thermal energy is transported more efficiently to the upper chromosphere and lower transition region and led to earlier heating of the lower atmosphere. Additionally, in González-Avilés et al (2017, the authors investigated the importance of magnetic resistivity itself and its relation to the magnetic reconnection process on the formation and evolution of jet with Type II spicules' characteristics.…”
Section: Introductionmentioning
confidence: 99%